Flowering Phenology, Seed yield and its Quality in Palisade Grass [Brachiaria brizantha (A. Rich.)Stapf] - S. S. PARIHAR,; ANJALI KAK, (Seed Research, 2026)
Studies on flowering phenology and component of spikelet yield in Brachiaria brizantha under rain grown condition revealed that initial head emergence (IHE) started in the first week of August after the start of monsoon initiated growth during June end. Head density peaked in the third week of August when seed shedding was on the way. Seed yield was 710 and 571 kg/ha/year in 1998 and 1999, respectively. Dual dormancy mechanism was evident as scarification of the rigid husk by H,SO, enhanced germination indicating coat-imposed dormancy due to the rigid husk. However, the effectiveness of dormancy breaking treatments (viz. H₂SO₄ + GA, H₂SO₄ + KNO3) was reduced after 12 months of storage suggesting another mechanism of dormancy also in operation (physiological dormancy), which was overcome during after- ripening in storage. Low seed setting (28-32%) and germination (18-25%) and immediate shattering of seeds suggest that prevailing climatic conditions of the site were not favorable for quality seed production.